Sugarcane response to nitrogen application in a no burn harvesting system, in rotation with legumes, for a coastal tableland soil - Silva, Paulo Albuquerque (2019)
Incorporation of high carbon/nitrogen material, from sugarcane harvested without burn, and new sugarcane cultivars, recomended in the last years, may lead to higher recommendations for nitrogen fertilization. As nitrogen fertilization plays an important role in greenhouse gas emissions, one way to reduce these emissions can be the partial replacement of fertilizers with legumes rotating, with sugarcane. The objective of this work is to establish the recommendation of nitrogen fertilization for sugarcane harvested without burn, and cultivated in rotation with Crotalaria spectabilis. The evaluated treatments are: sugarcane varieties (RB 92579 and RB 867515), rotation with Crotalaria spectabilis, and N rates (0 and 60 kg ha-1 for first cicle and, in two subsequent rattons, 0, 60, 120 and 180. kg N ha-1). The response of sugarcane to Crotalaria rotation and application of 60 kg of N ha-1 is significant, indicating that sugarcane responds only to N fertilizer in the absence of legume. Nitrogen from fertilization results in quadratic response of sugarcane ratoons yield, setting recommended doses of 124 to 146 kg ha-1 of N for high yield materials.